A novel epigenetic drug conjugating flavonoid and HDAC inhibitor confer suppression of acute myeloid leukemogenesis. Issue 14 (30th July 2021) - Zhang, Juan; Gao, Xuefeng; Wei, Mingming; Li, Yonghui; Yang, Guang; Yang, Cheng; Yu, Li
Abstract: Epigenetic dysregulation has long been identified as a key driver of leukemogenesis in acute myeloid leukemia (AML). However, epigenetic drugs such as histone deacetylase inhibitors (HDACis) targeting epigenetic alterations in AML have obtained only limited clinical efficiency without clear mechanism. Fortunately, we screened out a novel epigenetic agent named Apigenin–Vorinostat-Conjugate (AVC), which provides us a possibility to handle the heterogeneous malignancy. Its inhibition on HDACs was presented by HDACs expression, enzyme activity, and histone acetylation level. Its efficacy against AML was detected by cell viability assay and tumor progression of AML mouse model. Apoptosis is the major way causing cell death. We found that AVC efficiently suppresses leukemogenesis while sparing the normal human cells. Kasumi-1 cells are at least 20-fold higher sensitive to AVC (IC50 = 0.024 μM) than vorinostat (IC50 = 0.513 μM) and Ara-C (IC50 = 0.4366 μM). Furthermore, it can efficiently regress the tumorigenesis in AML mouse model while keeping the pivotal organs safe, demonstrating a feasibility and favorable safety profile in treatment of AML. Collectively, these preclinical data suggest a promising potential utilizing flavonoid–HDACi-conjugate as a next-generation epigenetic drug for clinical therapy against AML.